2022
DOI: 10.3389/fpls.2022.1061112
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Beneficial effects of fungal endophytes in major agricultural crops

Abstract: Editorial on the Research TopicBeneficial effects of fungal endophytes in major agricultural crops Endophytic fungi and agricultureEndophytic microorganisms are those that can dwell within plant tissues without any external sign of infection or other harmful effects on the host plants (Burragoni and Jeon, 2021). In recent decades, the important role that both bacterial and fungal endophytes play in plant growth and development, as well as in their ability to survive in their environment, has been identified (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Amino acids play a crucial role in microbial interactions as well as in plant growth. They act as signaling molecules in various metabolic cascades and help in cell-to-cell communication ( Frey-Klett et al., 2011 ; Poveda et al., 2022 ). The analysis of various amino acids was done using LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids play a crucial role in microbial interactions as well as in plant growth. They act as signaling molecules in various metabolic cascades and help in cell-to-cell communication ( Frey-Klett et al., 2011 ; Poveda et al., 2022 ). The analysis of various amino acids was done using LC-MS/MS.…”
Section: Discussionmentioning
confidence: 99%
“… Asim et al. (2022) observed increased root and aerial biomass, root and stem length, vigor index, and germination using wheat ( Triticum aestivum ) and endophytic fungus Fusarium oxysporum ( Asim et al., 2022 ; Poveda et al., 2022 ). It has also been reported that inoculating plants with S. indica or Arbuscular mycorrhizal fungi (AMF) boosts photosynthetic efficiency by increasing the chlorophyll content of leaves, surface area of leaves, stomatal conductance, and sugar content of leaves ( Das et al., 2012 ; Baishya et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The application to crops of micro‐organisms from extreme environments is a rapid, cost‐effective and environmentally‐friendly approach that could provide a better alternative to transgenic plants (Ray et al, 2019) and might augment the sustainable agriculture practices required by the new green revolution (Gopal & Gupta, 2016; Pozo et al, 2021). Despite these potential benefits, the use of microbial inoculants is not widespread in farming, mostly probably because of the strict regulatory standards for the registration and commercialization of new bioformulations, the difficulties of mass production, the efficacy of inoculants when applied under field conditions, and resistance from consumers and farmers who prefer traditional food production methods (Poveda et al, 2022). Moreover, there are still few reports of the mechanisms by which endophytes manipulate host plant physiology and exert their effects (Chaudhary et al, 2022; Sarkar et al, 2021), generating further questions about their use in crop production.…”
Section: Discussionmentioning
confidence: 99%
“…For example, those from coastal and geothermal settings confer tolerance to salt and heat, respectively, a phenomenon termed ‘habitat‐adapted symbiosis’ ( sensu ; Rodriguez et al, 2008), which is thought to arise from the activation of distinct metabolic pathways under specific selective pressures (Ballesteros et al, 2020; Rodriguez et al, 2008). Crop performance in MTEs might therefore be enhanced by endophytes from arid and saline soils, such as those in desert, montane and Antarctic environments (Bertini et al, 2022; Poveda et al, 2022). Although these underexplored environments are largely untapped because of their geographic isolation and inhospitable conditions, they are considered to be rich sources of endophytes (Saikkonen et al, 2004) that might synthesise a plethora of natural products capable of enhancing host stress tolerance (Tiwari & Bae, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation